Using multimedia e-learning materials to suplement teaching and learning of Mandarin Chinese language / Goh Chin Shuang … [et al.] - Goh, Chin Shuang; Tengku Shamsudden, Tengku Azeezeen; Thambyraja, Magarete Thresa; Ibrahim, Zainuddin (Research Management Institute (RMI), 2010)
The research sought to define the usability of Conversational Mandarin Chinese 1 as an interactive multimedia e-learning supplementary instructional tool in the teaching and learning of Elementary Mandarin (I) in UiTM, Shah Alam. Discussions regarding the characteristics of Conversational Mandarin Chinese 1 were derived from its contents, its relevance to the teaching and learning of language, its general design elements and students' motivation to learn, as well as the strengths and weakness of Conversational Mandarin Chinese 1 and the suggestions of improving multimedia e-learning instructional materials. This multimedia e-learning materials Conversational Mandarin Chinese 1 was a pilot prototype project and it was a selfdeveloped product by the researchers of this project to supplement conventional teaching and learning method of the Elementary Mandarin learning program in UiTM. Besides, it was offered as a self-helped learning instruction for the students, in view of the limitation of contact hours for third language classes in the university…